MODERN REQUIREMENTS FOR THE PRINCIPLES OF EDUCATIONAL ORGANIZATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article analyzes the modern requirements for the principles of educational organization.